The Experimental Study on Effects of Height and Hold up on performance of Vertical Gas-Liquid Separator using Amin Contactor Tower - Naderipour, Iman; khorshidi, Jamshid (Ciência e Natura, 2015)
In present research, first the treatment of flow in designed vertical gas-liquid separator and Amin contactor tower at refinery in order to reduce of liquid percent was simulated. In order to simulation was used three dimension model with finite volume method numerically. Then separator and contactor tower has been modeled three dimensional and for droplet tracking in continuous phase has been used discrete phase model (DPM) with turbulence RNG k-Ɛ model. Also the gambit software is used for three dimension designs and fluent is used for solution governing equations of flow field. After simulation, the governing model of separator and contactor tower, fluid flow, the effect of growing of liquid droplet, droplet settling length (disengagement time) was studied. After analysis and compare behavior of flow in separator and tower, the results of simulation compared with experimental results at sweetening unit in Sarkhoun and Qeshm gas treating company that has 95% compatibility. The simulation results has shown that TOTAL method has more compatibility with relation to other methods so that one of effective parameters in improvement of separation process is growing of liquid droplets and separation factor depend on that, also more disengagement time causes increase hold up time and finally growing of liquid droplets. Additionally according to younger's comment gas-liquid separators can applied in horizontal or vertical status so that he founded if L/D be 1.7 to 3.6, the separators should be used vertically also Branan has proved that if L/D > 5, a horizontal separator should be used. The results of research are shown that in special conditions with L/D>6.5 can apply vertical separator. Finally experimental data has shown that the settling length can be 36 ft (11m) that separation works well and according to Schiman this length should be 0.75D or a minimum 12in (0.305 m) whereas Gerunda recommends a length equal to the diameter or a minimum of 3 ft (0.914 m) that present result is new recommendation.